PERKEMBANGAN ISLAM DI AMERIKA SERIKAT - Rahmat, Rahmat (RIHLAH, 2013)
United Statesis asecularcountry, but it givesan opportunityto everyreligiontogrowandthrive. U.S. governmentimplemented policiesneed tobe a referencetothe Muslimminority areasinIndonesiaandother countries. The development of IslaminAmericacan not be separatedfromthe roleof theIslamicscholarsthere. Muslims, especiallythe charactersneed togiveattention tothe development of Islamandobservethe very rapidpropagationconceptsofferedin the landof Uncle Sam, especiallylately, interested persons fromamong therespectedandeducatedas well asthe natives. Moreover,a variety ofMuslimlifeintheUnited Statesneeds to be studiedmore in depth, such asthe relationship of Islamtoother religions, the role ofIslamic scholarsin theUnited States, educationalinstitutionsandmethods ofpropagationaredeveloped.Â